Green Brands and the Consumer Purchasing Intention Based on the example of the Body Shop in Taiwan - XU, YALUN (2011)
In recent decades, people’s life styles have significantly changed in comparison to what they used to be. Due to global warming and climate change, people are becoming more and more aware of environmental issues. This individual awareness has extended to impact the business world. Firms are increasingly paying more attention to the issues of social responsibility, and as part of this are trying to build a “green brand”. Therefore, this research will firstly attempt to clarify the relationship between a green brand and consumer behaviour. Secondly, it will discuss the kinds of situation that have the potential to influence consumers’ selection and purchase of a brand with green concepts. This dissertation will then examine a selection of consumer behaviour theories that assist in explaining consumer purchasing behaviour, in relation to green brands. Finally, this thesis will make practical suggestions and recommendations on how companies can implement green branding.